A test of our understanding of the ozone chemistry in the arctic polar vortex based on in-situ measurements of ClO, BrO, and O3, in the 1994/95 winter - Woyke, T.; Müller, R.; Stroh, F.; MacKenna, A. R.; Engel, A.; Margitan, J. J.; Rex, M.; Carslaw, K. S. (Journal of Geophysical Research: Atmospheres, 1999)
We present an analysis of in situ measurements of ClO, BrO, O-3, and long-lived tracers obtained on a balloon flight in the Arctic polar vortex launched from Kiruna, Sweden, 68 degrees N, on February 3, 1995. Using the method of tracer correlations, we deduce that the air masses sampled at an altitude of 21 km (480 K potential temperature), where a layer of enhanced ClO mixing ratios of up to 1150 parts per trillion by volume was observed, experienced a cumulative chemical ozone loss of 1.0+/-0.3 ppmv between late November 1994 and early February 1995, This estimate of chemical ozone loss can be confirmed using independent data sets and independent methods. Calculations using a trajectory box model show that the simulations underestimate the cumulative ozone loss by approximately a factor of 2, although observed ClO and BrO mixing ratios are well reproduced by the model. Employing additional simulations of ozone loss rates for idealized conditions, we conclude that the known chlorine and bromine catalytic cycles destroying odd oxygen with the known rate constants and absorption cross sections do not quantitatively account for the early winter ozone losses infered for air masses observed at 21 km.